Seasonal flooding, topography, and organic debris interact to influence the emergence and distribution of seedlings in a tropical grassland. (30th March 2018) - Bao, Francielli; Elsey‐Quirk, Tracy; de Assis, Marco Antonio; Arruda, Rafael; Pott, Arnildo
Abstract: In seasonally flooded wetlands, inundation and associated organic debris deposition followed by a drawdown period can promote plant community diversity across space and time. Post‐flood regeneration might be influenced by the direct effect of flooding on seed dispersal and seedling emergence, as well as the indirect effect of organic debris on seed trapping and germination. Our objective was to examine the influence of seasonal flooding, topography, and organic debris cover on seedling distribution in a seasonally flooded grassland. We measured species richness, seedling abundance, and organic debris cover for 3 yr in a seasonally flooded grassland in the Pantanal, Brazil, at three topographic levels at the end of the flood season and during the dry season when there was no debris deposition. A total of 43 species were recorded, with no difference in species richness detected between seasons. However, the abundance of some species was higher post‐flood than during the dry period. The greatest seedling abundance and richness were found post‐flood at intermediate elevations, followed by high and the lowest elevations. Seed germination and seedling establishment were likely suppressed at low topographic positions due to shading from organic debris and poor drainage. Therefore, areas with predictable annual floods promote diversity by creating spatial and temporal variations in environmental conditions.